Pemanfaatan Air Leri dan Air Mikroorganisme Lokal Sebagai Pengendali Rayap Tanah - Surahmaida, Surahmaida; Yuliarni, Floreta Fiska (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Termites (Coptotermes curvignathus) are considered more dangerous than other termite species as they can cause significant damage to plantation and agricultural crops, with widespread distribution. The use of chemical pesticides to control this pest can lead to resistance and have negative impacts on the environment and human health. An environmentally friendly solution involves utilizing natural plants/substances as botanical insecticides, such as rice washing water and local microorganism (MOL) water. The aim of this research is to evaluate the effects of these two substances on termite population control and determine the optimal formulation that can act as a termite repellent. and to determine the optimal formulation as an anti-termite. The research methodology involves determining formulations of botanical insecticides, namely 100% rice washing water, 100% MOL water, 50% rice washing water : 50% MOL water, 75% rice washing water : 25% MOL water, 25% rice washing water : 75% MOL water. Each test box is filled 5 soldier termites and 20 worker termites, then provided with test papers that have been soaked in the predetermined formulation. Each treatment is repeated three times and observed every 24 hours for 72 hours. The research results indicate that all formulations uses did not have a significant impact on termite mortality. It can be concluded that the use of rice washing water and MOL water in the tested formulations is not effective as an insecticide to control termite.